Sorption characteristics of economically viable silicate sorbents for sequestration of lead ions from aqueous solutions; Resource-Efficient Technologies; Vol. 3, iss. 3 - Yarusova S. B.; Gordienko P. S.; Krishna R. Ramya; Azarova Yu. A.; Suponina A. P.; Perfilev A. V.; Yogesh Chandra Sharma (2017, 2017)
Title screen